Hospital facilities, occupational safety environment and self-efficacy as predictors of healthcare-associated infections prevention and control compliance in nurses of inpatient care units - Luh Yulia Adiningsih; Ni Made Sri Nopiyani; Made Ady Wirawan (Public Health and Preventive Medicine Archive, 2018)
Background and purpose: The implementation of healthcareassociated infections (HAIs) prevention and control program in hospitals remains sub-optimal. The present study aims to determine the relationships between nurse’s self-efficacy, hospital’s occupational safety environment, and the availability of facilities, with the compliance on HAIs prevention and control in hospital inpatient care units. Methods: Cross-sectional survey was conducted with 128 nurses selected using systematic random sampling at Buleleng District Hospital’s inpatient care units. Data collection was conducted in March 2018 using self-administered questionnaires. The questionnaire consisted of five sections including characteristics of respondents, HAIs prevention and control practices, self-efficacy, occupational safety environment and the availability of facilities. Bivariate analysis was conducted to calculate the Pearson correlation coefficients between variables. Multivariate analysis was performed with multiple linear regressions to examine self-efficacy, occupational safety environment and availability of facilities as predictors of the compliance on HAIs prevention and control. Results: The study shows that 56.2% of nurses reported good compliance on HAIs prevention and control practices. Bivariate analysis shows a significant correlation between HAIs prevention and control compliance scores and self-efficacy (r=0.45; p=0.00), occupational safety environment (r=0.53; p=0.00), and the availability of facilities (r=0.65; p=0.00). Multivariate analysis shows that the availability of facilities is a significant predictor of HAIs prevention and control compliance (β=0.49; p<0.01) while self-efficacy and the occupational safety environment are also found to be significant predictors, although with lower standardized coefficients: β=0.16 (p=0.03) and β=0.17 (p=0.04), respectively. Conclusion: The significant predictors of compliance on HAIs prevention and control are availability of facilities, self efficacy and hospital’s occupational safety environment. This study highlights the importance of optimizing the availability of facilities, improving the occupational safety environment, and enhancing nurses’ self-efficacy in order to reduce the incidence of HAIs in hospitals.